EFFECT OF SUBSTITUTION OF GADOLINIUM ATOMS ON THE TWO-SLAB STRUCTURE OF SCANDATES BaGd2−хDyxSc2O7 - Titov, Y.A.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
The conditions of isovalent substitution of Gd atoms for Dy atoms in the A-positions of the BaGd2Sc2O7 two-slab perovskite-like structure of the BaGd2–xDyxSc2O7 type (0 < x ≤ 0.4) have determined by X-ray powder diffraction methods. Tetragonal crystal structure (space group P42/mnm) of the BaGd2–xDyxSc2O7 phases with x equal to 0.2, and 0.4 was determined by the Rietveld method. The crystal structure of BaGd2–xDyxSc2O7 is based on two-dimensional (infinite in the XY plane) perovskite-like blocks with a thickness of two slabs of deformed ScO6 octahedra connected by vertices. Ba atoms are located only at 4f position inside the perovskite block, while rare earth element atoms are located only at position 8j at the perovskite block boundary. The adjacent perovskite-like blocks are separated by a slab of (Gd,Dy)O9 polyhedra and held together by —O—(Gd,Dy)—O— interblock bonds. It is established that the isovalent substitution of Gd atoms by smaller Dy atoms leads to an increase in the degree of deformation of the interblocks polyhedra (Gd,Dy)O9. Such structural changes destabilize the interblock “crosslinking” and are one of the main reasons for the destruction of the slab perovskite-like structure of BaGd2–xDyxSc2O7 phases at x > 0.4. The research results could be used for purposeful regulation of structurally dependent properties of materials based on the BaGd2Sc2O7 scandate.